Stem Cells in Myelodysplastic Syndromes and Acute Myeloid Leukemia: First Cousins or Unrelated Entities? - Joudinaud, Romane; Boyer, Thomas (Frontiers in Oncology, 2021)
Myelodysplastic syndromes (MDSs) are associated with a significant risk of transformation to acute myeloid leukemia (AML), supported by alterations affecting malignant stem cells. This review focuses on the metabolic, phenotypic and genetic characteristics underlying this dynamic evolution, from myelodysplastic stem cells (MDS-SCs) to leukemic stem cells (LSCs). MDS-SCs are more likely to be derived from healthy hematopoietic stem cells (HSCs), whereas LSCs may originate from healthy progenitors, mostly LMPP (lymphoid-primed multipotential progenitors). Moreover, overexpression of CD123 and CLL1 markers by LSCs and MDS-SCs in high risk-MDS [HR-MDS] has led to exciting therapeutic applications. Single-cell sequencing has suggested that clonal evolution in the stem cell compartment was non-linear during MDS initiation and progression to AML, with pre-MDS-SC acquiring distinct additional mutations in parallel, that drive either MDS blast production or AML transformation. In AML and HR-MDS, common metabolic alterations have been identified in malignant stem cells, including activation of the protein machinery and dependence on oxidative phosphorylation. Targeting these metabolic abnormalities could prevent HR-MDS from progressing to AML. Strikingly, in low risk-MDS-SC, the expression of ribosomal proteins is decreased, which may be accompanied by a reduction in protein synthesis.